2021
DOI: 10.1037/cou0000437
|View full text |Cite
|
Sign up to set email alerts
|

Does person-group fit matter? A further examination of hope and belongingness in academic enhancement groups.

Abstract: Efforts have been made to support the academic success and address the retention of low academically performing college students; however, little is known about how these interventions are effective. This study builds upon recent findings that the hope and belongingness of college students in a group-based academic enhancement intervention were important factors in their academic success. Applying personenvironment fit theory, this study assessed changes in an individual's hope and belongingness, changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Research indicates that experiencing microaggressions decreases confidence, which in turn reduces college, graduate, and career aspirations (Acevedo-Gil, 2018). Additionally, experiencing microaggressions reduces feelings of belongingness (Lewis et al, 2021), which is a key factor for retention and academic success (Graham & McClain, 2019; Wurster et al, 2021; Yorke, 2016). Coping with microaggressions in an academic setting requires a great deal of emotional and cognitive energy (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that experiencing microaggressions decreases confidence, which in turn reduces college, graduate, and career aspirations (Acevedo-Gil, 2018). Additionally, experiencing microaggressions reduces feelings of belongingness (Lewis et al, 2021), which is a key factor for retention and academic success (Graham & McClain, 2019; Wurster et al, 2021; Yorke, 2016). Coping with microaggressions in an academic setting requires a great deal of emotional and cognitive energy (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other contexts of belonging, college belonging influences many life outcomes. For example, it is positively associated with academic and social self-efficacy (Wurster et al, 2021) as well as better physical health and more health-promoting behaviors (Walton & Cohen, 2011). Belongingness can also function as an emotional support for students processing difficult events such as loss of loved ones (McNally et al, 2021).…”
Section: Applied Studies Of College Belongingmentioning
confidence: 99%
“…(2020) emphasize the need for institutions to proactively create a sense of belonging for women of color, in particular, and to provide social and structural support through policies and systemic training efforts that address social pain. Findings indicated that academically struggling students benefited from participating in a mentor program, thus underscoring the importance of instilling belongingness (Capstick et al ., 2019; Hoyert et al ., 2019; Wurster et al ., 2021). Students of varying social identities experience college differently, yet institutional supports tend to be one-size-fits-all.…”
Section: Review Of Literaturementioning
confidence: 99%